PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Ester Sriulina Tarigan; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This study aims to examine the influence of intellectual capital and its main components on the financial performance of the company. Furthermore, this study also aims to test whether the IC contribution to the financial performance of the company does not differ among different sub-sectors. This study uses Partial Least Square (PLS) and one-way ANOVA test as a method of analysis to test the research hypothesis. The data used in this study is secondary data in the form of corporate financial statements in 2013-2015 obtained from Indonesia Stock Exchange. The population of this study is a financial sector company listed on the Indonesia Stock Exchange in 2013-2015. Sample in the research are 58 companies which is taken using purposive sampling method with some criteria of sample selection. The results of this study indicate that, when using firm size and leverage as control variable, human capital efficiency has a negative and significant impact on financial performance, structural capital efficiency has a positive and significant impact on financial performance, and capital employed efficiency has a positive and significant impact on financial performance. In addition, the results of this study indicate that there are significant differences in financial performance among different sub-sectors.